Trimetazidine MR in Patients with Stable Angina in Bangladesh - Islam, MN; Bashar, MA; Mahmud, jRS; Farid, N; Chowdhury, AW; Islam, KHQ; Bari, MS; Dhar, SC; Hoque, MS; Rahman, MT; et al. (University Heart Journal, 2008)
The TRIUMPHâ BANGLA (TRImetazidine MR in patients with stable angina: Unique Metabolic APproacH in BANGLAdesh) study was developed to provide information on the effect of trimetazidine modified release (MR) in patients with stable effort angina in Bangladesh. This medium term open-label, uncontrolled study was conducted in 88 patients with stable angina. Patients were treated with trimetazidine MR (35 mg tablet, twice a day) for 12 weeks in addition to their existing treatments. Overall 88 patients with stable angina (78 male and 10 female) aged 49.7 Â± 7.5 years had completed the study. During the 12-week treatment period the number of angina attacks per week decreased significantly from 7.3 Â± 6.6 to 2.1 Â± 4.8 (p < 0.0001). Concurrently the number of nitroglycerine use per week also decreased significantly from 4.1 Â± 4.5 to 0.9 Â± 1.5 (p < 0 .0001). Patientsâ quality of life, assessed on the Seattle Angina Questionnaire scores showed significant improvement (p < 0.0001) from before treatment to after treatment for all five items evaluated - physical limitation from 57.7 Â± 12.4 to 66.8 Â± 10, angina stability from 24.7 Â± 20.6 to 59.6 Â± 15.2, angina frequency from 41.2 Â± 21.8 to 63.4 Â± 15.7, treatment satisfaction from 44.5 Â± 21.8 to 57.9 Â± 18.8 and disease perception from 50.7 Â± 16.1 to 64.3 Â± 14.9. None of the patients reported any adverse effect during the treatment period. The results of this study suggest an improvement in clinical efficacy and quality of life with good tolerance of trimetazidine MR at a dose of 35mg twice a day for 12 weeks in patients with stable angina in Bangladesh. University Heart Journal Vol.4(1) January 2008